Land is heaven and earth: toward an ethics of land for South Africa: an exegetical study of Revelation 21:1-8 - Masondo, Sibusiso Theophilus (Department of Religious Studies, 2024)
This is an exegetical-hermeneutical study of Rev. 21:1- 8. The purpose of the present study is to develop an ethics of land for South Africa. Land is a hermeneutical key to understanding Rev. 21:1-8. One of the concerns in this study is that, although models have been proposed to deal with the land problem [be they legal, political, economic, agricultural], they have failed to deal with the ethical dimension. In this study a sociolinguistic methodology, particularly anti-language, has been adopted. Sociolingistics looks at connections between language and society. Language is a social and cultural phenomenon shaped by the values and norms of society and is used to construct social reality. Anti-language is the language generated by a group of people who do not see themselves as part of the mainstream social order. This language is anti-status quo. The African understanding of land is anti-language because it negates the mainstream Western understanding of land. To Africans land is not simply real estate but it has surplus value, and the surplus value is that which connects people to the land. It is this surplus value which many a model has failed to address. The idea of Newness in Revelation 21:1-8, is a classic case of the use of anti-language. It negates the present order of things. It shows a complete break with the past and the creation of the new reality which will serve the interests of the anti-social group. Despite the hardships experienced by the Johannine group, John is able to see the creation of a new order. This is the language of resistance to an oppressive system. There will be a qualitative difference between the Old and the New. God, in the new reality, is not transcendent or removed from the people, but He resides among His people. There is hope for the future.